BRAZILIAN TAX STRUCTURE AND ITS EFFECTS ON GENDER INEQUALITIES - Cristina Pereira Vieceli; Róber Iturriet Avila (Revista de Economia Contemporânea)
ABSTRACT: The objective of this study is to analyze whether the Brazilian tax model reinforces gender and class inequalities in the country. To do so, in addition to conducting a theoretical review, we analyze data from the Household Budget Survey (2017-2018) and the 2020 Brazilian income tax return. We conclude that the Brazilian tax structure reinforces gender and class inequalities in the country. Female taxpayers pay higher rates of income taxes and female-headed households pay higher rates of indirect taxes, whereas the totality of direct taxes show a higher tax incidence in male-headed households. As for the distribution of taxes by class, the analysis carried out by income decile indicates that families in the lowest decile pay the highest indirect and total tax burden when compared to all other deciles. The total direct tax burden falls more on families at the top but remains less than 10%, indicating the strong tax regressivity of Brazil.